Adverse events encountered during clinical placements by undergraduate nursing students in Spain. - García-Gámez, Marina; Morales-Asencio, José Miguel; García-Mayor, Silvia; Kaknani-Uttumchandani, Shakira; Martí-García, Celia; López-Leiva, María Inmaculada; León-Campos, Álvaro; Fernández-Ordóñez, Eloísa; García-Guerrero, Alfonso María; Iglesias-Parra, María Rosa (Elsevier, 2020)
Objectives: To describe the profile of adverse events encountered and the risks facing nursing students in clinical practice, as well as the severity and incidence of these events. Observational retrospective longitudinal study. Clinical placements of undergraduate nursing students from the University of Málaga, in hospitals and primary health care. A total of 4284 undergraduate nursing students, enrolled during seven consecutive years (2011-2018). Methods: Study data were obtained from students' notifications of adverse events during their clinical placements. The form for making this notification is available online, in the virtual campus for the practicum and notification is mandatory. Results: A total of 1638 reports of adverse events were made during the study period. The adverse events most commonly reported were clinical accidents, followed by sharp and needle-stick injuries, and medication errors. By clinical settings, adverse events occurring in critical care were most frequently reported (35.9%). By the severity of the event, the largest proportion (32.4%) were classified as serious. By the risk of recurrence, 49.8% of the events reported were classified as accidents that "could happen again at some time". In this respect, there were significant differences among the respondents, with fourth-year students reporting up to four times more events of this type than second and third-year students (p < 0.001). Conclusions: Nursing students are subject to clinical safety-related events during their practices, mostly concerning medication errors and sharps and needlestick injuries. The pattern of these events changes over time, as students evolve in their competences. To improve clinical safety competencies among student nurses, priority attention should be paid to medication management, dose calculations and reactions to situations of aggression and violence in healthcare settings.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/16720
Keywords: Estudiantes de enfermería; Enfermería - Medidas de seguridad; Education; Nursing; Graduate; Medication errors; Patient safety; Safety management